Intercanine Distance (ICD) Measurement Using Metric Analysis And Digital Imaging in Bite Mark Gender Identification - Prastyo, Eko (Indonesian Journal of Legal and Forensic Sciences (IJLFS); Vol 12 No 1 (2022): Indonesian Journal of Legal and Forensic SciencesDO - 10.24843/IJLFS.2022.v12.i01.p04, 2022)
This study aims to determine a gender using Intercanine Distance (ICD) measurement on bite marks with digital imaging and metric analysis. This is a Narrative Literature Review on 11 articles that meet the research requirements, and articles obtained from PubMed, Science Direct, and Wiley databases. It was found that the ICD of men and women measured with metric analysis and digital imaging was significantly different. Therefore, it was suggested that metric analysis is an excellent method to identify gender on bite marks compared to digital imaging, this method is practical, low budget, quick, and accurate.